2006
DOI: 10.1021/pr050414x
|View full text |Cite
|
Sign up to set email alerts
|

The Human Muscle Proteome in Aging

Abstract: The aim of the present study was to assess age-dependent changes of proteins in the vastus lateralis muscle of physically active elderly and young subjects by a combination of two-dimensional difference gel electrophoresis, SDS-PAGE and ESI-MS/MS. The differences observed in the elderly group included down-regulation of regulatory myosin light chains, particularly the phosphorylated isoforms, a higher proportion of myosin heavy chain isoforms 1 and 2A, and enhanced oxidative and reduced glycolytic capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
151
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(183 citation statements)
references
References 45 publications
(69 reference statements)
29
151
1
2
Order By: Relevance
“…Following separation by standard 2-DE, the abundance of key mitochondrial markers, such as ATP synthase and isocitrate dehydrogenase, was increased in the DT fraction. This would agree with an age-related shift to more oxidative metabolism in a slower-twitching fibre population [13][14][15]. Differential effects on individual protein spots representing muscle creatine kinase and prohibitin indicate altered post-translational modifications, such as phosphorylation patterns, in these proteins during muscle aging [42].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Following separation by standard 2-DE, the abundance of key mitochondrial markers, such as ATP synthase and isocitrate dehydrogenase, was increased in the DT fraction. This would agree with an age-related shift to more oxidative metabolism in a slower-twitching fibre population [13][14][15]. Differential effects on individual protein spots representing muscle creatine kinase and prohibitin indicate altered post-translational modifications, such as phosphorylation patterns, in these proteins during muscle aging [42].…”
Section: Discussionsupporting
confidence: 68%
“…Several mass spectrometry-based proteomic studies have investigated changes in the protein complement of aging skeletal muscles over the last few years, as reviewed by Doran et al [13]. These proteomic profiling studies have focused on crude soluble extracts and have shown that muscle aging is associated with altered expression levels of many key contractile proteins, regulatory elements, ion handling proteins, metabolic enzymes and mediators of the cellular stress response [14][15][16][17][18][19][20]. The proteomic finding of a drastically decreased density and reduced enzymatic activity of certain glycolytic enzymes in senescent fibres [21] is in agreement with the idea of a fast-to-slow transformation process during aging [13].…”
Section: Introductionmentioning
confidence: 99%
“…ATP synthase expression also increased with advancing age in the trophocytes and fat cells of workers. Previous studies have reported similar findings, showing that ATP synthase expression increases with advancing age in the brains and muscle of rats (Nicoletti et al 1995;Chang et al 2007;Doran et al 2008;Donoghue et al 2010), and in muscle of humans (Gelfi et al 2006). Although ND1 and ATP synthase expression measured in absolute terms increased with advancing age in the trophocytes and fat cells of workers, the relative expression of ND1 and ATP synthase normalized to mitochondrial density and VDAC1 was not significantly different.…”
Section: δψMsupporting
confidence: 73%
“…The proteomic profiling of crude soluble extracts has revealed a severely perturbed protein expression pattern in aged muscles involving enzymes of various metabolic pathways, regulatory components of ion homeostasis and elements of the cellular stress response (Piec et al, 2005;Gelfi et al, 2006;O'Connell et al, 2007;Doran et al, 2008;Lombardi et al, 2009;Capitanio et al, 2009). Altered post-translational modifications affecting tyrosine nitration, tyrosine/threonine phosphorylation and N-glycosylation were recently documented to occur to a large extent during biological aging of skeletal muscle fibres (Kanski et al, 2005;Gannon et al, 2008;O'Connell et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%